Foreign economic relations and economic growth in Portugal : a long term view - Fontoura, Maria Paula (2022)
This paper is a summary of some recent contributions to the study of Portuguese international economic relations. It presents a general overview of the main features of the evolution of protection, foreign trade and economic growth in Portugal between the early 19th century and the late 20th century. The analysis focuses on some puzzling aspects of that evolution before the Second World War and on the debate between the import substitution and export-led growth strategies of the Portuguese development policy after the Second World War. It concludes that, as a rule, protectionist measures hindered economic growth, and free-trade measures fostered economic growth. Moreover, important inefficiencies caused by protectionism, which helped to preserve traditional patterns of specialization and to delay modernization, are identified both before and after the Second World War.